Analisis Unsur Intrinsik dan Ekstrinsik pada Novel “Dia Adalah Kakakku” Karya Tere Liye - Putri, Anisa; Hasibuan, Abdullah (Sintaks: Jurnal Bahasa & Sastra Indonesia, 2023)
The qualitative descriptive method was utilized to analyze the intrinsic elements present in the novel "Dia adalah Kakakku" by Tere Liye. These intrinsic elements include the thematic focus, the main character Laisa, along with supporting characters such as Mamak, Dalimunte, Ikanuri, Wibisana, Yashinta, Wak Burhan, and Cie Hui. The setting is divided into various locations such as Lahambay valley, Wilderness Jungle, Upper Village, District City, river, house, school, airport, and hospital, with the story unfolding at night. The language style adopts the metamonia language style, employing the third-person point of view "he." The plot involves stages of setting, conflict, and resolution, conveying a message of perseverance, patience, determination, and responsibility. Additionally, the study also considers extrinsic elements.